(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
When managing any commercial, professional, scientific, or other project, it is necessary to plan all segments to integrate the various components and achieve the set plans. Nowadays, tasks such as drawing Gantt charts, network diagrams, and creating project reports are unthinkable without computer programs. The development of project management programs simplifies this work, allowing project team members to focus on project tasks, develop plans and strategies, and assess risk. In addition to project management computer programs that can be used for various projects, some programs have been developed specifically in the fashion and apparel industry. This paper focuses on the comparative analysis of programs developed specifically for project management in the fashion and textile industry and presents their specific features.